THE MAIN PRINCIPLES OF THE ART OF GRIME IN THE WORLD THEATER - Rizayeva Robiya Abdukakhor Qizi (Western European Studies, 2024)
This article discusses the importance of make-up in theater art, the early form of theatrical make-up and religious ritual events, and the make-up of Ancient Greek theater, Ancient Roman theater, Indian theater, Chinese theater make-up, No and kobuki Japanese theater make-up
Keywords: makeup; artist; artistic image